Strategi Pengembangan Pembelajaran Berbasis Proyek pada Mata Kuliah Manejemen Arsip Dinamis: Studi Kasus di Prodi Pendidikan Administrasi Perkantoran - Mutmainnah, Sri (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This research aims to develop and analyze the effectiveness of Project-Based Learning strategy (PjBL) in the Dynamic Archives Management course in the Study Program of Office Administration Education. PjBL is applied to improve students' ability in managing dynamic archives, both in terms of theory and practice. The method used is quantitative, with data collection through pretest and posttest before and after the implementation of PjBL. The results of the research showed a significant increase in students' abilities, with an increase in posttest scores compared to pretests. In addition to improving technical skills, PjBL also helps students develop collaboration, problem-solving and leadership skills. Most students showed consistent improvement, although some struggled with time management and cooperation. The archive management projects completed by students showed more systematic and efficient results. The conclusion of this research is that PjBL is effective in improving students' competency in managing dynamic archives, while strengthening soft skills including teamwork and communication. This approach can be widely applied in office administration education.